A Typology of Virtual Reality Locomotion Techniques - Costas Boletsis; Dimitra Chasanidou (Multimodal Technologies and Interaction, 2022)
Researchers have proposed a wide range of categorization schemes in order to characterize the space of VR locomotion techniques. In a previous work, a typology of VR locomotion techniques was proposed, introducing motion-based, roomscale-based, controller-based, and teleportation-based types of VR locomotion. The fact that (i) the proposed typology is used widely and makes a significant research impact in the field and (ii) the VR locomotion field is a considerably active research field, creates the need for this typology to be up-to-date and valid. Therefore, the present study builds on this previous work, and the typology’s consistency is investigated through a systematic literature review. Altogether, 42 articles were included in this literature review, eliciting 80 instances of 10 VR locomotion techniques. The results indicated that current typology cannot cover teleportation-based techniques enabled by motion (e.g., gestures and gazes). Therefore, the typology was updated, and a new type was added: “motion-based teleporting.”